Pengembangan Aplikasi M-Commerce Penjualan Kosmetik Berbasis Android - Ramli; Dody Hidayat (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2024)
The term is synonymous with the beauty of women. When talking about the beauty of it is inseparable from beauty products for women, or better known as cosmetic. Nowadays there are so many beauty cosmetics manufacturer company that offers so much convenience to the woman to keep her looks, well, cosmetic companies inside or outside the country. But not all cosmetics are sold freely in the market, especially cosmetics that come from abroad. Often the cosmetic consumers find it very difficult to buy cosmetics wanted since there is limited access to these cosmetics. For the mobile application aims to simplify cosmetic consumers find and buy cosmetics wanted. This mobile application can also promote cosmetics and shops selling cosmetics with promotional costs much cheaper. So expect to further cosmetic consumers can purchase their favorite cosmetics more easily and also can increase sales of cosmetics stores and cosmetics manufacturers themselves.